"The wandering life I led" : essays on Hortense Mancini, Duchess Mazarin and early modern women's border crossings - Shifrin, Susan, 1961- (Cambridge Scholars Pub., 2009)
This book of essays brings together international scholars working on the literary, visual, musical, and theatrical representations and reception of Hortense Mancini, Duchess Mazarin, an early modern woman whose literal-geographical-"border crossings" serve here as the starting point for an investigation of her and others' elisions and transgressions of borders of all kinds. The authors lay out strategies for exploring the ways in which she crossed geographical, gendered, cultural, and-in sch ...